Long-Term Results in Scalp Tissue Expansion in Children - Maillet-Declerck, Marie; Calibre, Clotilde; Herbaux, Bernard; Duquennoy-Martinot, Véronique (European Journal of Pediatric Surgery, 2012)
Introduction Tissue expansion is frequently used in scalp repair in children. The short-term complications are well known and described in the literature. Impacts at a distance such as potential deformation of the skull or widening of the scar are not so often presented. The aim of this study is to analyze the results at a distance and the actual impact after scalp tissue expansion in young children.Materials and Methods We clinically reviewed 15 children operated on between May 2002 and April 2008 for scalp tissue expansion.Results Mean follow-up was 3 years and 5 months, and mean age of the patients at the first surgery was 20 months. In 11 cases, we observed a widening of the scar. Only two patients presented with a slight flattening of the skull. All parents were satisfied with the results. Children do not remind or keep no unpleasant memory of the surgical protocol.Discussion Only rare studies focused on very young children. Most of surgeons fear about the consequences of scalp tissue expansion on cranial bone and thus on cerebral growth in children under the age of 2. But it appears that cranial changes in young children are transient with a return to normal within 6 months after removing the implant. Another common problem is the scar enlargement. According to our results and the review of the literature, it seems essential to perform the suture in two layers associated to local reconstruction on the scar to provide the best cosmetic outcomes.Conclusion Tissue expansion remains a good technique to repair large lesions of the scalp in children. The deformation of the skull spontaneously resolves and does not have any consequence on brain growth. The widening of the scar is a common problem in children but can be reduced by suture in two layers associated with local reconstruction. Moreover, young children do not keep any unpleasant memory of this period and are not susceptible to social pressure.
Keywords: scalp tissue expansion; children; skull deformation; scar enlargement